2012
DOI: 10.2147/ceg.s23926
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of esomeprazole in treating acid-related diseases in Japanese populations

Abstract: Esomeprazole (Nexium®; AstraZeneca), the S-isomer of omeprazole, is the first proton pump inhibitor (PPI) to be developed as an optical isomer. Compared with omeprazole, esomeprazole has an improved pharmacokinetic profile with regards to CYP2C19 (S-mephenytoin 4′-hydroxylase) genotype, showing increased systemic exposure and less interindividual variability. Further, esomeprazole is a more potent acid inhibitor than other currently available PPIs and is therefore used as a first-line drug for acid-related dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 71 publications
0
15
2
Order By: Relevance
“…As newer generations PPIs, esomeprazole suggested less influence by CYP2C19 genotype than other proton pump inhibitors, but the fraction through CYP2C19 metabolism was about 70% [21]. The PK studies showed that the AUC of esomeprazole in CYP2C19 PM phenotypes was 3-fold higher than in individuals with NM phenotypes [22]. In the current study, the proportion of PM phenotypes in HPAG was 23.08% and no patient in LPAG.…”
Section: Discussionmentioning
confidence: 60%
“…As newer generations PPIs, esomeprazole suggested less influence by CYP2C19 genotype than other proton pump inhibitors, but the fraction through CYP2C19 metabolism was about 70% [21]. The PK studies showed that the AUC of esomeprazole in CYP2C19 PM phenotypes was 3-fold higher than in individuals with NM phenotypes [22]. In the current study, the proportion of PM phenotypes in HPAG was 23.08% and no patient in LPAG.…”
Section: Discussionmentioning
confidence: 60%
“…One important characteristic that could potentially affect patient outcome is CYP2C19 genotype. Although we did not determine the genotypes of the patients, as the CYP2C19 genotype reportedly does not change the pharmacokinetics of either vonoprazan or esomeprazole dramatically, the CYP2C19 genotype is unlikely to influence the present results. Some clinical characteristics, such as H. pylori infection, ulcer size >1200 mm 2 , and ulcer location, can prolong ulcer healing .…”
Section: Discussionmentioning
confidence: 81%
“…After the advent of omeprazole in 1989, PPIs have been recognized to be more effective clinically than histamine-2 receptor antagonists (H2RAs), 1 and a number of PPIs have been developed. 2 Esomeprazole, the S-isomer of omeprazole, also known as NEXIUM ® . Esomeprazole was developed to provide further improvement on efficacy for acid-related diseases with higher systemic bioavailability due to the less first-pass metabolism and lower plasma clearance.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%